1986
DOI: 10.3171/jns.1986.65.6.0779
|View full text |Cite
|
Sign up to set email alerts
|

Dermoid tumors occurring at the site of previous myelomeningocele repair

Abstract: Four children with previously repaired myelomeningoceles presented toward the end of the first decade or early in the second decade of life with deteriorating lower-extremity and bladder function. Myelography and computerized tomography scanning demonstrated irregular filling defects at the area of the myelomeningocele repair, and surgical exploration disclosed dermoid tumors that were adherent to the placode and adjacent roots. Dermoid tumors should be considered in the differential diagnosis of neurological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 3 publications
2
23
1
3
Order By: Relevance
“…Van Gilder and Schwartz 13 produced dermoids experimentally in young rats by implantation of skin fragments. This theory was supported in human beings by other authors that reported the occurrence of such tumors secondary to implantation of dermal fragments into spinal subarachnoid space by accidental trauma 14 , lumbar puncture 15 or surgery 16 . Our case is interesting because the adult patient with chronic low back and leg pain and intestinal dysfunction presented with two distinct dermoids located at the lumbosacral region.…”
Section: Fig 3 Histological Analysis Of the Specimens [A] Abundant supporting
confidence: 71%
“…Van Gilder and Schwartz 13 produced dermoids experimentally in young rats by implantation of skin fragments. This theory was supported in human beings by other authors that reported the occurrence of such tumors secondary to implantation of dermal fragments into spinal subarachnoid space by accidental trauma 14 , lumbar puncture 15 or surgery 16 . Our case is interesting because the adult patient with chronic low back and leg pain and intestinal dysfunction presented with two distinct dermoids located at the lumbosacral region.…”
Section: Fig 3 Histological Analysis Of the Specimens [A] Abundant supporting
confidence: 71%
“…2,5,12 They may occur with or without associated pathology (dysraphism or trauma) or by iatrogenic introduction during lumbar puncture. 1,7 They may also occur after operative procedures for spinal fracture associated with CSF leakage 10 and after operations for spinal dysraphism including repair of myelomeningocele, 9 lipomyelomeningocele, 11 and (exceptionally) with meningocele, 13 as in our patient. Epidermoids diagnosed in patients with prior spinal surgery can be related to either iatrogenic introduction of cells or underlying present ectodermal rests, particularly with a diagnosed meningocele, which carries an association with dermoid/epidermoid tumors.…”
Section: Postoperative Coursementioning
confidence: 98%
“…3,8 A series of these by Scott et al posits that dorsally located dermoids or epidermoids after myelomeningocele repair could be attributed to iatrogenic implantation of tissue, whereas the ventrally located tumors were a result of congenital dermal inclusions. 9 Symptomatic epidermoids are treated surgically. These histologically benign ectodermal rests may recur locally.…”
Section: Postoperative Coursementioning
confidence: 99%
“…They may rupture spontaneously 4 by trauma, or during surgery 5 . Spinal dermoid tumours can be associated with bony malformations, myelomeningoceles, hypertrichosis and/or dermal sinus tract 6 .…”
Section: Discussionmentioning
confidence: 99%